Loss- and gain-of-function analyses reveal the essential role of Cyp19a1 in ovarian determination of the red-eared slider turtle. - Jiadong Shen; Wei Sun; Kaiyue Wu; Tianyi Zhuang; Jiandong Lei; Qinglu Ma; Ling Xiao; Chutian Ge (Genetics, 2023)
Estrogen signaling exerts a decisive role in female sex determination and differentiation in chicken and fish. Aromatase encoded by Cyp19a1 is the key enzyme that catalyzes the conversion of androgen to estrogen. Correlative analyses implicate the potential involvement of aromatase in reptilian sexual development, however, the direct genetic evidence is lacking. Herein, we found that Cyp19a1 exhibited temperature-dependent sexually dimorphic expression, and located in the medullary somatic cells in early female embryos of the red-eared slider turtle (Trachemys scripta elegans), before the gonad is distinct. To determine the functional role of Cyp19a1 in turtle ovarian determination, we established loss- and gain-of-function models through in ovo lentivirus-mediated genetic manipulation. At female-producing temperature, inhibition of aromatase or knockdown of Cyp19a1 in turtle embryos resulted in female-to-male sex reversal, with the formation of a testis-like structure and a male distribution pattern of germ cells, as well as ectopic expression of malespecific markers (SOX9 and AMH) and disappearance of ovarian regulator FOXL2. On the contrary, overexpression of Cyp19a1 at male-producing temperature led to male-to-female sex reversal. In conclusion, our results suggest that Cyp19a1 is both necessary and sufficient for ovarian determination in the red-eared slider turtle, establishing causality and a direct genetic link between aromatase and reptilian sex determination and differentiation.